Pengaruh Insentif, Budaya Organisasi dan Lingkungan Kerja Terhadap Kedisiplinan Karyawan Pada PT. Aldakara Jaya Karya - Fatah, Abdul; Fatah, Putri Fachri Aulia; Iqbal, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine incentives, organizational culture, and work environment on employee discipline at PT. Aldakara Jaya Karya. The independent variabels in this research are Incentives, Organizational Culture and Work Environment and the dependent variabel is Employee Discipline. And this research method uses descriptive and associative quantitative methods. The data sources are primary data and secondary data. The research was carried out from December 2018 to May 2019. The research population was 81 in the Event Organizer (EO) division, the sample was 81 people. Data was collected using a questionnaire. To test the model and hypothesis using SPSS.24.0. Based on the results of the analysis, the following results were obtained: 1) incentives, organizational culture and work environment have a positive and significant effect on employee discipline, both partially and jointly at PT. Aldakara Jaya Karya. The results of this research recommend that employee discipline can be improved, especially through organizational culture with the dimension that employees always try to be responsible for solving work problems without waiting for orders from superiors